Peran Komunikasi Interpersonal Perawat Gigi Dalam Pelayanan Kesehatan Gigi Dan Mulut Di Sekolah Dasar - Abubakar, Syamsuddin; Saleh, Muh; Annida Sahrani, Andi (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Interpersonal communication plays an important role in delivering oral health education, especially to elementary school children who face challenges in understanding health information. This study aimed to analyze the role of dental nurses’ interpersonal communication in improving students’ knowledge and behavior regarding oral health at SD Negeri 27 Samaelo, Pangkep Regency. This research used a descriptive-analytic quantitative approach with a pre-experimental one-group pre-test and post-test design. The study sample consisted of 43 students from grades V and VI, selected through purposive sampling. Data were collected using pre-test and post-test questionnaires and analyzed descriptively and inferentially using a paired t-test. The results showed a significant increase in the mean score from 60.47 in the pre-test to 91.16 in the post-test. Statistical analysis yielded a p-value < 0.05, indicating a significant effect of dental nurses’ interpersonal communication on improving students’ understanding and changing their behavior in maintaining oral health. In conclusion, effective interpersonal communication plays a crucial role in enhancing knowledge and encouraging positive behavioral changes among students regarding oral health care. This study is expected to serve as a reference for developing oral health education strategies in elementary schools to support the promotion of healthy living behaviors from an early age.